Patellar tendon mechanical properties adaptation to a resistance training protocol measured by elastography - Mannarino, Pietro (2019)
The patellar tendon is one of the most relevant in the human body because of its fundamental importance in gait and orthostatism. Its mechanical properties are closely related to quadriceps function, its usual overload and training programs to which it is subjected. This study evaluates the adaptation of the patellar tendon´s shear modulus to an 8-week resistance training program, using supersonic shear wave imaging (SSI) elastography in 15 healthy young men. In addition, the variations of the vastus lateralis´ shear modulus and thickness, the morphological adaptations of the patellar tendon and the increase of knee extensor torque were measured using B-mode ultrasound and dynamometry. The observed results attest the efficiency of the resistance training program applied to promote strength gains and hypertrophy, but did not reveal statistically significant adaptations in the shear modulus or thickness of the patellar tendon. A pronounced and statistically significant increase was observed in the vastus lateralis´ shear modulus. This study may serve as a basis for further investigations into intervention protocols aimed to adapt the knee extensor mechanism for injury prevention, rehabilitation or conditioning.